A clinician's personal view of assisted reproductive technology over 35 years - Yovich, John (2011)
This invited presentation is intended to cover clinical developments in the evolution of assisted reproductive technology (ART), a process which was attempted during the 1940's and 50's and culminated in the fi rst fruition in 1978. The fi rst in vitro fertilisation (IVF) child ensued following the partnership by a scientist with a focussed ambition (Nobel laureate Robert Edwards) joining with the gynaecologist who introduced laparoscopy to Britain in the late 60's (Patrick Steptoe). My journey commenced in 1976 as a clinician who became immersed in the embryological and endocrinological science, whence most progress in ART emanates, and continued into a medical directorship position from which this personal view is documented. Several clinical advances have been important developments in the understanding and management of sub-fertile patients. However evolution of the various laboratory sciences has been the major key essential to meeting both the immediate as well as the long-term needs for humanreproduction. The future requires a much better understanding and control over gametogenesis and a laboratory process which much more closely duplicates intrinsic reproductive physiology, avoiding gamete and embryo exposure to the atmosphere. © 2011 by the Society for Biology of Reproduction.